2012
DOI: 10.1134/s1063783412040038
|View full text |Cite
|
Sign up to set email alerts
|

Yield strength of nanocrystalline materials under high-rate plastic deformation

Abstract: A high rate plastic deformation of fine grained materials has been considered as a result of com peting processes of dislocation gliding in the grains and grain boundary sliding. A structural model has been proposed for describing the grain boundary sliding as a dominant mechanism of plasticity of nanocrystalline metals. The dependence of the yield strength on the material properties, temperature, and deformation rate has been studied numerically. For the adequate description of the experimental data and molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…In fact, an analytical work by Borodin et al [46] also suggested that the viscous effect is still a dominant factor at high strain rates even in nano-materials. In such cases, the boundary viscosity acts as the viscous source for plastic deformation.…”
Section: Viscous Drag Under Dynamic Loadingmentioning
confidence: 95%
“…In fact, an analytical work by Borodin et al [46] also suggested that the viscous effect is still a dominant factor at high strain rates even in nano-materials. In such cases, the boundary viscosity acts as the viscous source for plastic deformation.…”
Section: Viscous Drag Under Dynamic Loadingmentioning
confidence: 95%
“…Actually, analytic works by Borodin et al [82] and Weinberger et al [83] also suggested that the viscous effect is even a dominant factor during high strain rate deformation even in NC materials. In such case, the boundary viscosity acts as the viscous source for plastic deformation.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with (Borodin and Mayer, 2012;Krasnikov et al, 2011;Mayer et al, 2013), the total annihilation rate of dislocations per unit volume of substance can be expressed in…”
Section: Kinetics Of Twinsmentioning
confidence: 99%